Pemuridan dalam Perjanjian Baru: Sebuah Eksplorasi Teologi Biblika tentang Pemuridan Wanita dalam Injil Markus - Victor Baitanu (Jurnal Arrabona, 2024)
Not so many people talk about female discipleship, not even Indonesian theologians who have written about discipleship in the New Testament, in relation to the Gospel of Mark. Because the New Testament background also does not position Women as men do, and thus ignores the female disciples in the context of Jesus' ministry, some even say that because Jesus never ordained a woman to be an Apostle, on the other hand Women are also considered unfit because their duties and responsibilities are to conceive children, take care of the household and so on. To discuss this theme, the author uses a qualitative approach. The purpose of this study is to educate God's servants regarding the theological perspective in terms of the position of women in ministry. Through this research the author found that although  the Discipleship of Women in the New Testament not many people observe it, it is  taught by Scripture that the Female disciples followed Jesus from the beginning of his ministry to suffering, death (they knew the burial place), witnessing that Jesus rose from the dead. The Old Testament, although there were not so many women who were leaders in religious matters, but that does not mean there were none. For there is the Woman to whom the Lord speaks; for example, a prophetess named Deborah, Hulda. Thus it appears that God spoke not only to male prophets but also to prophetesses, as well as the New Testament, and even history records that Women were also involved in copying Scripture.